Sports Tourism in the New Normal - Martín-García, María del Mar; Ruiz-Real, José Luis; Gázquez-Abad, Juan Carlos; Uribe-Toril, Juan (Springer, 2024)
The global pandemic declared in 2020 has not only presented obstacles to the tourism industry, but it has also presented an opportunity to use resilience as a tool to reboot the sector. Sports tourism has risen to this challenge, using the circumstances of the new reality to highlight other aspects of sport and successfully address the new normal. In the context of the normalization of the pandemic, golf is emerging as a sports tourism trend in the new scenario. The promotion of sports would increase opportunities to revitalize golf tourism destinations. This study aims to explore the dimensions that influence the intention to play golf. Using a sample of 343 participants, a multiple linear regression analysis was conducted. The results suggest that the current increased importance placed on physical and mental health and playing sports in a safe environment may be the main reason for the increase in golf participation in this post-pandemic era.
Keywords: Turismo - Aspectos sociales; Golf tourism; New normal; Golf participation; Well-being